The effect of high- and low-intensity inspiratory muscle training on the physiological response to exercise in cross-country skiers - Klusiewicz, A.; Starczewski, M.; Zubik, L.; Dlugolecka, B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Aim: The aim of the study was to evaluate the impact of isolated respiratory muscle training (RMT) on the work capacity and changes in selected spirometric parameters in trained cross-country skiers. Methods: The study involved 4 female and 12 male skiers. A cross-over model was used: each subject belonged both to the group that completed 7 weeks of RMT training (the RMT group) and the one that completed 7 weeks of simulated RMT (the placebo group). Half of the subjects started by performing RMT and the other half by performing simulated RMT. Both RMT programmes consisted in performing 30 inspiratory manoeuvres twice a day, 6 days a week, using the heavy resistance model of POWERbreathe®. In the RMT group, resistance was gradually increased in subsequent weeks, whereas in the placebo group, resistance was set to 29 cmH2O (level 0) in the first week, and in the next six weeks it was set to a constant value of 53 cmH2O (level 1). All of the subjects underwent spirometric measurements and a stress test in the following stages of the study: before the experiment, after the change in RMT, and after the experiment. The spirometric measurements were used to determine i.a. maximal inspiratory pressure (PImax). The stress test was conducted on a ski ergometer, with a gradual increase in intensity, and was continued until exhaustion. Results: A significant increase in PImax and in the work performed in the stress test was observed in both the RMT and placebo group for male cross-country skiers, but only in the RMT group for female skiers. No significant differences in PImax or work were observed between the RMT and placebo group, regardless of the gender of the skiers. Conclusion: We found that completing a 7-week RMT programme did not cause an increase in the work capacity of trained skiers. The effects of RMT on improving PImax, which is indicative of the strength of the inspiratory muscles, depend on the magnitude of inspiratory resistance. The principle of gradually increasing inspiratory resistance according to a given person`s progress in training should be followed in implementing RMT. The study also showed that RMT did not have a considerable impact on breathing efficiency in maximal effort.